2017
DOI: 10.3389/fmicb.2017.01938
|View full text |Cite
|
Sign up to set email alerts
|

Morbid Sequences Suggest Molecular Mimicry between Microbial Peptides and Self-Antigens: A Possibility of Inciting Autoimmunity

Abstract: Understanding etiology of autoimmune diseases has been a great challenge for designing drugs and vaccines. The pathophysiology of many autoimmune diseases may be attributed to molecular mimicry provoked by microbes. Molecular mimicry hypothesizes that a sequence homology between foreign and self-peptides leads to cross-activation of autoreactive T cells. Different microbial proteins are implicated in various autoimmune diseases, including multiple sclerosis, human type 1 diabetes, primary biliary cirrhosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 94 publications
1
21
0
6
Order By: Relevance
“…A factor related to the involvement of E coli in the onset of PBC is the molecular homology between E coli and humans, as molecular homology is believed to play an important role in the activation of autoreactive T cells . We identified and compared the levels of human PDC‐E2‐specific TCR and E coli PDC‐E2‐specific TCRs in PBC patients and healthy controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A factor related to the involvement of E coli in the onset of PBC is the molecular homology between E coli and humans, as molecular homology is believed to play an important role in the activation of autoreactive T cells . We identified and compared the levels of human PDC‐E2‐specific TCR and E coli PDC‐E2‐specific TCRs in PBC patients and healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…A factor related to the involvement of E coli in the onset of PBC is the molecular homology between E coli and humans, as molecular homology is believed to play an important role in the activation of autoreactive T cells. 12,13 We identified and compared the levels of human PDC-E2-specific TCR and E coli PDC-E2-specific TCRs in PBC patients and healthy controls. It was worth noticing that there were many overlaps in the sequences between the TCRs recovered from human PDC-E2 stimulation versus E coli PDC-E2 stimulation.…”
Section: High Level Of E Coli (And Human Pdc-e2)specific Tcrs In Pbmentioning
confidence: 99%
“…Genetic factors, related to HLA antigens, could be another favoring factor, acting as restriction molecules for antigenic bacterial peptides presented to and cross recognized by cytotoxic CD8+ Tlymphocytes. Furthermore, these peptides possess a potential to skew the immune response toward Th1-like patterns [30].…”
Section: Discussionmentioning
confidence: 99%
“…Researches in RA patients or animal models indicated that the abundance of many genera of gut microbiome increased or decreased significantly compared with the control group (healthy people or animal). The influence mechanism of gut microbiome on the pathophysiology of RA may be multifactorial, and it mainly includes the following aspects: the ability to produce citrullinization of peptides by enzymatic action, activation of antigen-presenting cells through an effect on TLRs or NLRs, antigenic mimicry, control of host immune system (triggering T cell differentiation), alterations in permeability of intestinal mucosal, and increase of T helper type 17-mediated mucosal inflammation [Table 1 (Round et al, 2011;Marietta et al, 2016;Teng et al, 2016;Pahari et al, 2017;Guo et al, 2019;Li et al, 2020;McHugh, 2020;Tajik et al, 2020)].…”
Section: The Mechanism Of Gut Microbiome In Rheumatoid Arthritismentioning
confidence: 99%